A Novel In Vitro Mouse Model to Study Mycobacterium tuberculosis Dissemination Across Brain Vessels: A Combination Granuloma and Blood‐Brain Barrier Mouse Model. (27th July 2020) - Walter, Fruzsina R.; Gilpin, Trey E.; Herbath, Melinda; Deli, Maria A.; Sandor, Matyas; Fabry, Zsuzsanna
Abstract: In vitro culture models of the blood‐brain barrier (BBB) provide a useful platform to test the mechanisms of cellular infiltration and pathogen dissemination into the central nervous system (CNS). We present an in vitro mouse model of the BBB to test Mycobacterium tuberculosis (Mtb) dissemination across brain endothelial cells. One‐third of the global population is infected with Mtb, and in 1%‐2% of cases bacteria invade the CNS through a largely unknown process. The "Trojan horse" theory supports the role of a cellular carrier that engulfs bacteria and carries them to the brain without being recognized. We present for the first time a protocol for an in vitro BBB‐granuloma model that supports the Trojan horse mechanism of Mtb dissemination into the CNS. Handling of bacterial cultures, in vivo and in vitro infections, isolation of primary astroglial and endothelial cells, and assembly of the in vitro BBB model is presented. These techniques can be used to analyze the interaction of adaptive and innate immune system cells with brain endothelial cells, cellular transmigration, BBB morphological and functional changes, and methods of bacterial dissemination. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of primary mouse brain astrocytes and endothelial cells Basic Protocol 2 : Isolation of primary mouse bone marrow–derived dendritic cells Support Protocol 1 : Validation of dendritic cell purity by flow cytometry Basic Protocol 3 : Isolation of primary mouse peripheral blood mononuclear cells Support Protocol 2 : Isolation of primary mouse spleen cells Support Protocol 3 : Purification and validation of CD4+ T cells from PBMCs and spleen cells Basic Protocol 4 : Isolation of liver granuloma supernatant and determination of organ load Support Protocol 4 : In vivo and in vitro infection with mycobacteria Basic Protocol 5 : Assembly of the BBB co‐culture model Basic Protocol 6 : Assembly of the combined in vitro granuloma and BBB model